Antifouling biocides in German marinas: Exposure assessment and calculation of national consumption and emission - Daehne, Dagmar; Fürle, Constanze; Thomsen, Anja; Watermann, Burkard; Feibicke, Michael (Integrated environmental assessment and management, 2017)
ABSTRACT The authorization of biocidal antifouling products for leisure boats is the subject of the European Union Biocides Regulation 528/2012. National specifics may be regarded by the member states in their assessment of environmental risks. The aim of this survey was to collect corresponding data and to create a database for the environmental risk assessment of antifouling active substances in German surface waters. Water concentrations of current antifouling active substances and selected breakdown products were measured in a single‐sampling campaign covering 50 marinas at inland and coastal areas. Increased levels were found for Zn, Cu, and cybutryne. For the latter, the maximum allowable concentration according to Directive 2013/39/EU was exceeded at 5 marinas. For Cu, local environmental quality standards were exceeded at 10 marinas. Base data on the total boat inventory in Germany were lacking until now. For that reason, a nationwide survey of mooring berths was conducted by use of aerial photos. About 206 000 mooring berths obviously used by boats with a potential antifouling application were counted. The blind spot of very small marinas was estimated at 20 000 berths. Seventy‐one percent of berths were located at freshwater sites, illustrating the importance of navigable inland waterways for leisure boat activities and underlining the need for a customized exposure assessment in these areas. Moreover, the national consumption of all antifouling products for leisure boats was calculated. The total amount of 794 tonnes/annum (t/a) consisted of 179 t/a of inorganic Cu compounds, 19 t/a of organic cobiocides, and 49.5 t/a of Zn. With regard to weight proportion, 141 t/a Cu and 40 t/a Zn were consumed. Assuming an emission ratio of 50% during service life, 70.5 t/a of Cu amounted to 15% of all external sources for Cu release to German surface waters. These figures highlight the need for mitigation measures. Integr Environ Assess Manag 2017;13:892–905. © 2017 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC) Key Points Seventy‐one percent of the total berths used by leisure boats are situated at German freshwater sites. A survey on antifouling biocides in 50 marinas revealed the actual load situation. Cuprous compounds reached approximately 90% of consumed antifouling agents. Inputs of Cu emissions by leisure boats amount to 15% of all external sources of Cu released to German surface waters.